THU0608 Association between allopurinol dose-titration and serum uric acid levels in gout patients: us electronic health record data. (15th June 2017) - Fu, A-C; Taylor, DC; Reasner, DS
Abstract : Background: Allopurinol is a first-line urate lowering therapy for patients with gout. The American College of Rheumatology guidelines recommend allopurinol dose-titration to maintain serum uric acid (sUA) levels <6 mg/dl. Objectives: To understand allopurinol dose-titration relative to sUA levels. Methods: This retrospective study used the de-identified Humedica electronic medical record database. The study included all sUA and allopurinol records among gout patients (ICD-9-CM: 274.xx) ≥18 years old with first gout diagnosis in 2007 – 2015. An episode was defined as an allopurinol initial dose (ID) prior to (closest) and titrated dose (TD) after (within 30 days) an sUA test. Dose-titration was categorized as an episode with a dose-change (up-titration: ID < TD; down-titration: ID > TD), or no-dose-change (ID = TD). For multiple different doses recorded on the same prescription date, the sum of doses was taken as daily dosage. Episodes were considered uncontrolled when sUA ≥6 mg/dl. Descriptive episode-level analyses were performed. Results: Within 64, 609 episodes, 57% of episodes were uncontrolled (sUA: 6 to <8 mg/dl: 38%; 8 to <10 mg/dl: 15%; ≥10mg/dl: 4%). Seventy-one percent of uncontrolled episodes were no-dose-change, 21% were up-titrated, and 7% were down-titrated. Within no-dose-change episodes, 51% were uncontrolled and lower doses corresponded to higher percentages of uncontrolled episodes (<100mg/day: 88%; 100mg/day: 70%; >100, <300 mg/day: 49%; 300mg/day: 38%; >300mg/day: 36%). Seventy-eight percent of dose-change episodes were uncontrolled, of which 100 to 300 mg/day (39%) was the most frequent dose titration. Overall, the most frequent TD was 300 mg/day (52%) followed by 100mg/day (36%), >100 – <300mg/day (8%), >300mg/day (3%), and <100mg/day (<1%). Conclusions: Allopurinol dose is not generally titrated regardless of sUA control. This pattern suggests a need for active management of patients with gout with uncontrolled sUA including consideration of new treatment options in addition to allopurinol. References: Juraschek SP et al. Gout, urate-lowering therapy, and uric acid levels among adults in the United States. Arthritis Care Res (Hoboken). 2015 Apr;67(4):588–92. Khanna D et al. 2012 American College of Rheumatology guidelines for management of gout. Part 1: systematic nonpharmacologic and pharmacologic therapeutic approaches to hyperuricemia. Arthritis Care Res (Hoboken). 2012 Oct;64(10):1431–46. Acknowledgements: This study was funded by Ironwood Pharmaceuticals. Disclosure of Interest: A.-C. Fu Employee of: Employee of Ironwood Pharmaceuticals, D. Taylor Employee of: Employee of Ironwood Pharmaceuticals, D. Reasner Employee of: Employee of Ironwood Pharmaceuticals